A prospective study to evaluate the gender prediction of blastocysts by using cell-free DNA within a culture medium - Somayeh Barzanouni; Farideh Moramezi; Mahvash Zargar; Hamid Galehdari; Masoud Hemadi (Shahid Sadoughi University of Medical Sciences, 2022)
Abstract Background: Preimplantation genetic diagnosis (PGD) has been used as an option for couples with the possibility of having a baby with a genetic disorder. The common method for performing this test involves isolating 1 cell from day 3 or a few cells from day 5 embryos and performing genetic studies on the cell-extracted DNA. This method is invasive and can cause abortion after implantation in the uterus. Because of this, 2 noninvasive methods for performing a PGD have been studied: PGD using blastocyst fluid and PGD using embryo culture medium. Objective: The aim of this study is to determine the sensitivity of the polymerase chain reaction (PCR) technique to detect the Y chromosome using cell-free DNA within a culture medium for gender prediction of blastocysts. Materials and Methods: In this study, the gender of 30 embryos on day 5 was determined using embryonic DNA extraction from the culture medium and the PCR technique to evaluate the sex-determining region Y and fragile X mental retardation genes. Then, the accuracy was assessed using ultrasound. Results: The results of the PCR technique showed that 7 embryos were male, but an ultrasound revealed that 13 were male. Conclusion: The given results indicated that, because of the low amount of DNA extracted from the culture medium, the diagnosis of the existence of the Y chromosome by this method is still not accurate enough for detecting the gender of the embryo.